Sequential Triplex Real-Time PCR Assay for Detecting 21 Pneumococcal Capsular Serotypes That Account for a High Global Disease Burden - (:unkn) unknown (AMER SOC MICROBIOLOGY, 2013)
We developed and validated a real-time PCR assay consisting of 7 triplexed reactions to identify 11 individual serotypes plus 10 small serogroups representing the majority of disease-causing isolates of Streptococcus pneumoniae. This assay targets the 13 serotypes included within the 13-valent conjugate vaccine and 8 additional key serotypes or serogroups. Advantages over other serotyping assays are described. The assay will be expanded to 40 serotypes/serogroups. We will provide periodic updates at our protocol website.
Keywords: STREPTOCOCCUS-PNEUMONIAE SEROTYPES; MULTIPLEX PCR; INVASIVE DISEASE; IDENTIFICATION; DIAGNOSIS; CHILDREN; SAMPLES; 6A